Cross- linked enzyme aggregates of recombinantxylanase for hemicelluloses to xylooligosaccharides - Shalyda, Md Shaarani (2018)
Hemicelluloses are heterogeneous branched polymers of sugars that exist abundantly in nature. Enzymatic hydrolysis is envisioned as a highly potential method in converting hemicelluloses into fuels and value-added chemicals. However, the use of free enzyme is hampered by low operational stability, difficulty in recovery and non-reusability, which requires for enzyme immobilization. Carrier-bound immobilization leads to utilization of high cost matrices, clogging of filters during downstream processing and presence of large amounts of non-catalytic ballast. Therefore, cross-linked enzyme aggregates (CLEA), a carrier-free technology that combines purification (precipitation) and immobilization into a single operation and does not require purified enzymes, is the solution to these problems. In this study, a recombinant xylanase (Xyl) from Trichoderma reesei was immobilized using three approaches: Xyl-CLEA, Xyl-CLEA-BSA (bovine serum albumin) and Xyl-CLEAsilanized maghemite. The use of ethanol as precipitant (1:9 volume ratio of enzyme to precipitant), glutaraldehyde (0.2:1 of glutaraldehyde to enzyme of 100 mM concentration) as cross-linking agent and the introduction of (3-aminopropyl) triethoxysilane (APTES) silanized maghemite (0.0075:1 of silanized maghemite to enzyme) prevailed in forming xylanase CLEAs with good enzyme activity recovery (78 %), thermal stability (50 % retained activity) and reusability (50 % retained activity). The Xyl-CLEA-silanized maghemite enhanced the activity recovery 1.66- and 1.50-fold compared to Xyl-CLEA and Xyl-CLEA-BSA, respectively. At elevated temperature of 60 °C and pHs of 3.0 and 8.0, Xyl-CLEA-silanized maghemite achieved better stability compared to the other CLEAs and free enzyme. Xyl-CLEAsilanized maghemite also successfully retained more than 50 % of its activity after 6 cycles, whereas Xyl-CLEA only retained approximately 10 % after 5 cycles. Therefore, the performance of Xyl-CLEA-silanized maghemite was further investigated by xylan hydrolysis under optimised reaction conditions. Xylooligosaccharides yield was slightly improved by 1.26- fold compared to the free enzyme. Kinetic parameters confirmed that CLEA immobilization did affect the productivity of the designed biocatalyst.